Relaparotomy after Cesarean Section in a Tertiary Center - Poudel, Sandesh; Adhikari, Shree Prasad; Rai, Snigdha; Mishra, Sangeeta; Tamrakar, Renuka (Europasian Journal of Medical Sciences, 2021)
Background: Relaparotomy after cesarean section is associated with significant maternal morbidity and mortality which can be prevented with proper precaution during the primary surgery. The objective of the study was to determine factors associated with relaparotomy after cesarean section. Methods: A hospital based descriptive cross sectional study conducted by analyzing the records of 3 years from 1st July 2017 to 30th June 2020, among the women who underwent relaparotomy after cesarean section at Paropakar Maternity and Women’s Hospital, Kathmandu. Results: There were 21,270 cesarean sections among 64,475 deliveries with the mean incidence of 32.6%. A total of 22 patients underwent relaparotomy out of which 18 had their primary surgery performed at our hospital i.e. 0.08% of the total caesarean section, and 4 cases were referred from peripheries. 60% of primary surgery were done by residents and the commonest indications of primary surgery were previous CS (36.3%) and obstructed labor (27.2%). Primary PPH was the major indication for laparotomy (31.8%) with mean interval from primary surgery of 4.7 hours followed by burst abdomen (22.7%) and secondary PPH (18.1%). Hysterectomy was the commonest operative intervention done during relaparotomy accounting for 45.4% followed by tension suture for burst abdomen (18%). There were 2 maternal death among them which were due to aspiration pneumonia following eclapmsia and DIC. Conclusion: Relaparotomy has increased risk of adverse maternal outcome but still is a lifesaving intervention. Early recognition, timely intervention and multidisciplinary teamwork helps to decrease the complications associated with it.